2023
DOI: 10.3390/ijms24021577
|View full text |Cite
|
Sign up to set email alerts
|

An Active Bio-Based Food Packaging Material of ZnO@Plant Polyphenols/Cellulose/Polyvinyl Alcohol: DESIGN, Characterization and Application

Abstract: Active packaging materials protect food from deterioration and extend its shelf life. In the quest to design intriguing packaging materials, biocomposite ZnO/plant polyphenols/cellulose/polyvinyl alcohol (ZnPCP) was prepared via simple hydrothermal and casting methods. The structure and morphology of the composite were fully analyzed using XRD, FTIR, SEM and XPS. The ZnO particles, plant polyphenols (PPL) and cellulose were found to be dispersed in PVA. All of these components share their unique functions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The determination of material density is conducted by established techniques, such as the use of Archimedes' principle. Porosity, which refers to the extent of empty space within a given material, may be assessed by employing image analysis methodologies on microscopic or scanning electron microscope (SEM) pictures [31]. The evaluation of the colour and appearance of materials may be conducted through the utilisation of colorimeters or spectrophotometers.…”
Section: Materials Selection and Methodologymentioning
confidence: 99%
“…The determination of material density is conducted by established techniques, such as the use of Archimedes' principle. Porosity, which refers to the extent of empty space within a given material, may be assessed by employing image analysis methodologies on microscopic or scanning electron microscope (SEM) pictures [31]. The evaluation of the colour and appearance of materials may be conducted through the utilisation of colorimeters or spectrophotometers.…”
Section: Materials Selection and Methodologymentioning
confidence: 99%
“…Recent research has confirmed the presence of microplastic (∼240,000 particles per litre) in water bottles [ 9 ]. The demand to replace synthetic plastic with innovative biodegradable polymers that have large mechanical strength, thermally stable, reasonable optical transparency, UV resistant, antibacterial and antioxidant packaging materials is increasing [ 2 , 3 , 7 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For over a century, polyvinyl alcohol (PVA) has been known as one of the most highly produced synthetic biodegradable polymers [ 11 ]. The exceptional properties of PVA include non-toxicity, high transparency, flexibility, biocompatibility, and chemical resistance [ 10 , [12] , [13] , [14] , [15] , [16] , [17] ]. As a packaging material, PVA appears suitable for resolving environmental pollution problems and decreasing ecological waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation